ASSESSMENT OF FECUNDITY AND GONADOSOMATIC INDEX OF COMMERCIALLY IMPORTANT FISH, LABEO ROHITA FROM RAMGANGA RIVER - MOHAMMAD ALAM,; J.K. PATHAK, (International Journal of Pharma and Bio Sciences, 2010)
Present investigation deals with the assessment of Fecundity and Gonadosomatic index of Labeo rohita collected from Ramganga river of western Uttar Pradesh during June 2005 to May 2008. The mean value of fecundity was estimated as 66823.70 ± 4312.39 eggs with a mean total length of 183.06 ± 5.60 mm and mean total body weight of 315.64 ± 16.59 grams. The relationship of fecundity with other parameters such as Total length (TL), Total weight (TW), Ovary length (OL) and Ovary weight (OW) were found to be linear and the values of correlation coefficient (r) was 0.97, 0.97, 0.99 and 0.95 respectively. The average relative fecundity was calculated as 202.78 ± 3.75 Highest value of GSI was recorded in the month of August indicating spawning period of Labeo rohita.